One-Factor-at-a-Time (OFAT) Optimization of Victoria Blue R Dye Biodegradation by Pineapple Waste Garbage Enzymes - Lee, Jian-Rong; Jalani, Joyce Cynthia; Zatul Iffah, Mohd Arshad; Santos, José C.S. dos; Siti Kholijah, Abdul Mudalip; Shalyda, Md Shaarani; Siti Zubaidah, Sulaiman (Penerbit Akademia Baru, 2024)
Victoria blue R is a cationic triphenylmethane dye usually released from textile industries and reported to exhibit mutagenic and carcinogenic effects on aquatic organisms and humans. Hence, the objective of this study is to investigate the capability of pineapple waste garbage enzymes to biodegrade the Victoria blue R dye using One-Factor-At-a-Time (OFAT) optimization under the effect of Victoria blue R dye concentration (0.02 to 0.10 mg/mL), pH (1 to 7), and temperature (25°C to 49°C) via Design Expert 7.0 software. The results show that pineapple waste garbage enzymes gave the highest decolorization efficiency at a concentration of 0.07 mg/mL of Victoria blue R dye, pH 4.74, and 40.4°C. The ANOVA analysis suggests all models are quadratic, and the R-Squared values for the factors are 0.92, 0.95 and 0.92 for the concentration of Victoria blue R dye, pH and temperature, respectively. This work proposed that pineapple waste garbage enzymes can effectively remove Victoria blue R dye in wastewater applications.